2010
DOI: 10.4103/0019-557x.75739
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of knee osteoarthritis amongst perimenopausal women in an urban resettlement colony in South Delhi

Abstract: A community-based cross-sectional study was carried out in an urban resettlement colony in South Delhi to study the prevalence of knee osteoarthritis in women aged ≥40 years and treatment seeking behavior of women suffering from osteoarthritis. Osteoarthritis was diagnosed by using clinical criteria given by American College of Rheumatology for diagnosis of Idiopathic Osteoarthritis of knee joints. A total 260 women were interviewed out of which 123 (47.3%) women were found to be suffering from knee osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 1 publication
13
39
0
Order By: Relevance
“…Worldwide estimates are that 9.6% of men and 18.0% of women aged ≥60 years have symptomatic osteoarthritis where as in India it ranges from 14-47%. [1][2][3] The prevalence of osteoarthritis increases indefinitely with age, because the condition is not reversible. Before the age of 45, more men than women have osteoarthritis; after age 45, it is more common in women.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide estimates are that 9.6% of men and 18.0% of women aged ≥60 years have symptomatic osteoarthritis where as in India it ranges from 14-47%. [1][2][3] The prevalence of osteoarthritis increases indefinitely with age, because the condition is not reversible. Before the age of 45, more men than women have osteoarthritis; after age 45, it is more common in women.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is similar to that in other studies. 5,6,7 OA was more in women compared to men in our study (66% vs. 34% respectively). This difference can be possibly due to the lack of physical activity, mobility and higher prevalence of obesity among women in general.…”
Section: Discussionmentioning
confidence: 51%
“…8 Prevalence of osteoarthritis was higher among illiterate women 42 (52.5%) and it was also found to be higher among women belonging to upper lower socioeconomic class 36 (55.2%) as compared to study conducted by Salve H et al from Delhi which showed that the prevalence of osteoarthritis was found to be high in illiterate women as compared to literate women and it was also found to be higher among low socioeconomic class 32 (55.2%). 8 We also found that, among 66 women who had osteoarthritis, 68.2 % were currently on treatment and 16.70% were receiving treatment from government facility, 19.70% and 3% were seeking treatment from chemist and traditional healers respectively, 31.80% did not receive any treatment as compared to study conducted by Salve H et al from Delhi which showed that out of 123 women with osteoarthritis only 53 (43%) were currently on treatment, out of which 40 (78.4%)are receiving treatment from government facility whereas remaining participants were seeking treatment from private practitioners, chemist and traditional healers. More than half of women (57%) who were suffering from osteoarthritis did not seek any kind of treatment.…”
Section: Discussionmentioning
confidence: 58%